Mediating effect of self-efficacy on self-perceived burden and kinesiophobia in patients with coronary heart disease after percutaneous coronary intervention in China: a cross-sectional study - Feng Wang; Yu Wang; Jing Zhou; Mengyu He; Zhenyue Chen (BMJ Open)
Objectives To analyse the current state of kinesiophobia, self-perceived burden and self-efficacy in patients with coronary heart disease (CHD) following percutaneous coronary intervention (PCI). In addition, to study the mediating effect of self-efficacy between self-perceived burden and kinesiophobia.Design Cross-sectional study.Setting A tertiary-level hospital in Anhui Province, China.Participants We recruited a total of 255 patients for this study. The eligible subjects were patients diagnosed with coronary artery disease who underwent successful transradial PCI. The exclusion criteria included patients who had both diseases affecting their exercise ability and severe psychiatric disorders.Primary and secondary outcome measures We used questionnaires consisting of the Self-Efficacy Scale for Chronic Disease (SESC), the Tampa Scale for Kinesiophobia Heart (TSK-SV Heart), the Self-Perceived Burden Scale (SBPS) and a general information data sheet to obtain participant information. SPSS Bootstrap was used for mediated effects analysis.Results The total patient score for kinesiophobia, self-perceived burden and self-efficacy was 42.96±5.00, 24.36±7.84 and 7.61±1.46, respectively. Kinesiophobia was negatively and positively associated with self-efficacy (r=−0.368, p<0.01) and self-perceived burden (r=0.271, p<0.01), respectively. The mediating effect of self-efficacy between self-perceived burden and kinesiophobia in patients was 0.046 (95% CI 0.018 to 0.081), accounting for 26.59% of the total effect.Conclusion Self-efficacy partially mediates self-perceived burden and kinesiophobia in patients. The medical staff of facilities should strengthen the evaluation and monitoring of patients’ self-efficacy and self-perceived burden and conduct intervention measures to reduce their kinesiophobia.